Creating Indonesian Academic Vocabulary by Using the Ant Word Profiler Program to Academic Writing for BIPA Learning - Rhubido, Dadang; Shodiq, Syamsul; Asteria, Prima Vidya (Universitas Muhammadiyah Malang, 2023)
The list of Indonesian academic vocabulary has never been made. This study aims to create a list of Indonesian academic vocabulary. This study also explains how to create a list of academic vocabulary using the Ant Word Profiler program. The method used in this study is a combined research method (mixed methods), namely the combination of quantitative and qualitative methods. The research data used in this study were taken from 200 scientific articles from accredited national journals covering the fields of social, health, engineering, and life sciences. The research data amounted to 672,787 words. The stages of research data analysis are (1) knowing the list of Indonesian academic vocabulary, (2) making a list of Indonesian academic vocabulary (3) describing the research results. This researh produced a product in the form of a list of Indonesian academic vocabulary consisting of 235 word families. The list of academic vocabulary that has been made in this study can be used by BIPA teachers and students to be more effective and efficient in learning the Indonesian language so that it easier for BIPA students to produce academic texts in Indonesian.